On the phenomenological approach to the high temperature superconductors - Alascio, Blas Rafael; Proetto, Cesar Ramón (Comisión Nacional de Energía Atómica; Argentina)
Fil: Alascio, Blas Rafael Comisión Nacional de Energía Atómica; Argentina